2005
DOI: 10.1002/masy.200550810
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated Cationic Frontal Polymerization

Abstract: Photoactivated cationic ring‐opening polymerizations of certain oxirane and oxetane monomers take place in a frontal manner. The study of the frontal behavior of those monomers was conducted using a new analytical technique involving optical pyrometry that provides insight into the mechanism of these polymerizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…The same effect has been noted by Sasaki [23] for unsensitized photopolymerizations of this monomer carried out using short wavelength UV light. In a recent paper [24] , we have shown that oxetane monomers such as POX which display long induction periods undergo frontal polymerizations. A mechanism was proposed to explain this behavior.…”
Section: Cationic Photopolymerizations Using Curcumin Photosensitizationmentioning
confidence: 97%
“…The same effect has been noted by Sasaki [23] for unsensitized photopolymerizations of this monomer carried out using short wavelength UV light. In a recent paper [24] , we have shown that oxetane monomers such as POX which display long induction periods undergo frontal polymerizations. A mechanism was proposed to explain this behavior.…”
Section: Cationic Photopolymerizations Using Curcumin Photosensitizationmentioning
confidence: 97%
“…As example, the decrease of light penetration with increasing thickness represents a serious drawback for thick, pigmented coatings and fiber-reinforced composites. Therefore, the concept of dual-cure initiating systems based on both photo-thermal curing appears as a promising alternative to solve the issue [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Indeed, the combination of a photochemical polymerization promoting a thermal curing has rendered possible the curing of thick samples.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the thermal process can also be used to complete the curing of the epoxide resin in shadowed areas, typically in the case of 3D parts. In the best cases, the photochemical process would also speed up the thermal curing to perform a photoinduced thermal frontal polymerization [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Crivello and coworkers successfully utilized FP in thin reaction zones with certain oxirane and oxetane monomers by using photoactivated initiators [7,8]. While in previous studies of FP, the heat produced by the initial FP reaction was sufficient for the generation of a polymer front and for its subsequent self-propagation through the reactant mixture, experimentalists have witnessed that this is often not the case for thin reaction layers.…”
Section: Introductionmentioning
confidence: 99%